Automation of Website-Based Information and Advertising Services for Graha Medika Clinics: Otomatisasi Pelayanan Informasi dan Iklan Klinik Graha Medika Berbasis Website - Prayoga, Galang Ryan; Rosyid, Mochamad Alfan (Universitas Muhammadiyah Sidoarjo, 2020)
The development of this website-based media makes it easy for website users, both patients and doctors, to obtain information on the facilities and services offered by the Graha Medika Clinic as well as the convenience of consultation facilities provided to patients in chatting or consulting and registering online. This website application that has been built successfully displays information such as profiles of doctors, clinic facilities, doctor's schedules and online consultations or chats for patients. Based on the results of the questionnaire, respondents stated that by building this website-based media, patients and the general public, internet users, could easily get information about services and consultations with doctors.